2006
DOI: 10.1007/s00253-005-0082-y
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of tannase from Paecilomyces variotii: hydrolysis of tannic acid using immobilized tannase

Abstract: An extracellular tannase (tannin acyl hydrolase) was isolated from Paecilomyces variotii and purified from cell-free culture filtrate using ammonium sulfate precipitation followed by ion exchange and gel filtration chromatography. Fractional precipitation of the culture filtrate with ammonium sulfate yielded 78.7% with 13.6-folds purification, and diethylaminoethyl-cellulose column chromatography and gel filtration showed 19.4-folds and 30.5-folds purifications, respectively. Molecular mass of tannase was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 20 publications
8
47
2
2
Order By: Relevance
“…This observation is comparable with the earlier study by Mahendran et al [36] which showed that purified tannase from P. varoitii was present in a monomeric form the specific detection of tannase activity on the SDS-PAGE during zymogram analysis. Previously, Lactobacillus plantarum and K. pneumonia tannase were also found to be a monomer with a molecular mass of 46.5 and 50 kDa, respectively [37,38].…”
Section: Discussionsupporting
confidence: 82%
“…This observation is comparable with the earlier study by Mahendran et al [36] which showed that purified tannase from P. varoitii was present in a monomeric form the specific detection of tannase activity on the SDS-PAGE during zymogram analysis. Previously, Lactobacillus plantarum and K. pneumonia tannase were also found to be a monomer with a molecular mass of 46.5 and 50 kDa, respectively [37,38].…”
Section: Discussionsupporting
confidence: 82%
“…For example, the Paecilomyces variotii tannase is a monomeric enzyme with a molecular mass of only 45 kDa (Mahendran et al, 2006), whereas the A. oryzae tannase is an octamer, consisting of four identical heterodimeric units (Hatamoto et al, 1996) and the same tannase produced by P. pastoris forms single heterodimers (Zhong et al, 2004). The molecular mass of the native, glycosylated A. adeninivorans tannase was estimated here to be 320 kDa, implying that it comprises four subunits with molecular sizes of about 80 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…The crude tannase from Paecilomyces variotii was stable in a temperature range from 20 to 50 °C, in which it retained 99 and 96 % residual activity at 20 and 50 °C, respectively (13). The thermal stability profi le of crude tannase from Penicillium notatum NCIM 923 revealed that above 95 % was retained at 40 °C (53).…”
Section: Tannase Thermal Stabilitymentioning
confidence: 99%
“…Tannic acid, for example, is a hydrolysable tannin, which can be hydrolyzed by tannase to gallic acid and glucose. Among its applications are: preparation of instant tea (8), manufacture of beverages (juices, beer and wine) (11), production of gallic and ellagic acids (12), ester synthesis and effl uent processing (13), and as an additive for animal feed (14).…”
Section: Introductionmentioning
confidence: 99%